Frequency and Associated Factors of Post-dural Puncture Headache at a Tertiary Care Hospital of Southern Punjab, Pakistan - Maria Jabeen; Sohaib Hassan; Aneeqa Saad; Sohail Safdar (Pakistan Journal of Medical Research)
Background: Post-dural puncture headache is characterized as a headache that develops within five days following a lumbar puncture. Its onset is influenced by several contributing factors.